2022
DOI: 10.1002/sd.2290
|View full text |Cite
|
Sign up to set email alerts
|

How Sustainable Development Goals interlinkages influence European Union countries’ progress towards the 2030 Agenda

Abstract: The analysis of interlinkages between the sustainable development goals (SDGs) and the assessment of countries' progress towards the goals are two prominent research areas in the debate around the 2030 Agenda. The central questions are whether countries are progressing towards the goals at sufficient speed, and whether the SDGs can be achieved in their entirety. While it is evident that trade‐offs between the 2030 Agenda's objectives might prevent countries from achieving all 17 SDGs simultaneously, the extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…An important point when using a general interaction model is therefore to adapt the initiative in question such that synergies are accelerated, and the trade‐offs are redesigned to become another initiative's synergistic fuel. This is in line with the recent study by Kostetckaia and Hametner (2022), who found that it is crucial to tackle the question of how trade‐offs can be overcome and ideally turned into synergies in order to ensure the achievement of the SDGs in their entirety.…”
Section: Discussionsupporting
confidence: 86%
“…An important point when using a general interaction model is therefore to adapt the initiative in question such that synergies are accelerated, and the trade‐offs are redesigned to become another initiative's synergistic fuel. This is in line with the recent study by Kostetckaia and Hametner (2022), who found that it is crucial to tackle the question of how trade‐offs can be overcome and ideally turned into synergies in order to ensure the achievement of the SDGs in their entirety.…”
Section: Discussionsupporting
confidence: 86%
“…Synergies are identified by positive correlations, whereas the correlations that identify trade‐offs are negative (Pradhan et al, 2017). Most recently, Kostetckaia and Hametner (2022) reveal that trade‐offs have a greater influence than synergies upon the progress of an overall SDG, suggesting that overcoming trade‐offs is more important than enhancing synergies.…”
Section: The Holistic View Of Development: Sdgs As a Nested Conceptmentioning
confidence: 99%
“…The first step is therefore to identify suitable indicators to represent sustainability in the transport sector and the availability of these data. The use of Eurostat was used for this purpose (Kostetckaia and Hametner, 2022; Streimikis and Balezentis, 2020). Analyzing the various indicators proposed in this database the need to select only those indicators suitable for the objective is evident.…”
Section: Methodsmentioning
confidence: 99%